Analysis of Cultural Values in Ayam Semur as Traditional Food in Ternate - Syamsia, Syamsia (Universitas Negeri Medan, 2025)
The aim of this research is to know about the Cultural Ayam Semur as traditional food in the Ternate, Traditional food serves as an essential representation of a community’s cultural identity, embodying values passed down through generations. Ayam semur, a well-known traditional dish in Ternate, holds significant cultural meanings beyond its culinary purpose. This study aims to analyze the cultural values embedded in ayam semur and its role in Ternate’s social and traditional practices. The reseatcher use a qualitative research approach, data were collected through interviews, observations, and literature reviews involving cultural experts, local elders, and community members. The findings reveal that ayam semur represents prosperity and blessings, as it is often served during traditional ceremonies, including weddings and communal gatherings. The preparation and sharing of ayam semur also reflect the values of solidarity, mutual cooperation (gotong royong), and respect for elders, as it is traditionally prepared collectively and served in a hierarchical manner. Additionally, ayam semur carries spiritual and religious significance, as it is often accompanied by prayers, symbolizing gratitude and divine blessings. Keywords: ayam semur; cultural values; traditional food.